2016
DOI: 10.1088/0957-0233/27/12/125104
|View full text |Cite
|
Sign up to set email alerts
|

Intensity liquid level sensor based on multimode interference and fiber Bragg grating

Abstract: In this paper an intensity liquid level sensor based on a single-mode—no-core—single-mode (SMS) fiber structure together with a Bragg grating inscribed in the later single mode fiber is proposed. As the no-core fiber is sensitive to the external refractive index, the SMS spectral response will be shifted related to the length of no-core fiber that is immersed in a liquid. By positioning the FBG central wavelength at the spectral region of the SMS edge filter, it is possible to measure the liquid level using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Another method where no-core fiber is embedded into a conventional single-mode fiber was used as liquid level indicator in Ref. 137. Bragg gratings were inscribed in one part of the single-mode fiber that will be dipped in liquid.…”
Section: Fbg-based Liquid Level Sensormentioning
confidence: 99%
“…Another method where no-core fiber is embedded into a conventional single-mode fiber was used as liquid level indicator in Ref. 137. Bragg gratings were inscribed in one part of the single-mode fiber that will be dipped in liquid.…”
Section: Fbg-based Liquid Level Sensormentioning
confidence: 99%
“…Therefore, simultaneous measurement can be achieved using a sensitivity matrix, which can be calculated using Eq. ( 15) and ( 16) [27,28,29]. Here, φ peak6 and φ peak7 represent the phase variations caused by changes in temperature (δT) and strain (δS) .…”
Section: B Transmission Typementioning
confidence: 99%
“…Generally speaking, liquid-level sensors based on fiber gratings and interference effects can achieve a high sensing resolution, but the sensing range is small. Examples of such sensors include multimode interferometers [6][7][8][9][10], Mach-Zehnder interferometers [11][12][13], anti-resonance reflecting optical waveguides [14,15], Fabry-Perot interferometers [16], fiber Bragg gratings [17,18], and long-period fiber gratings [19,20]. In 2011, Antonio-Lopez et al reported a no-core fiber (NCF) liquid-level sensor based on the self-image effect of multimode interference [6].…”
Section: Introductionmentioning
confidence: 99%